Urgency of the Role of Parents Against the Use of Gadgets in Children of Primary Education - Istna Listiyani; Nurulfat Riani; Bening Brilianty Pamungkas (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
In the 21st century, the use of gadgets is increasing. Many advantages are offered with advances in increasingly sophisticated technology. It is not spared from that most of the use of gadgets is even misused by children of Primary Education age. Basically, the use of gadgets by minors starts from the family environment itself. If at the time the children are addicted to gadgets will cause growth retardation and other psychological disorders. This study aims to analyze the role of parents in the use of gadgets by Primary Education age children. The research method is a literature study. The results of the study are the role of parents as first and foremost educators for children is very important to control the use of gadgets in everyday life carried out by children. The conclusion of this research is the role of parents greatly influences the use of gadgets for Primary Education age children